2007
DOI: 10.1021/jm070811e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Properties of Novel 2-Aminopyrimidin-4(3H)-ones Highly Potent against HIV-1 Mutant Strains

Abstract: Following the disclosure of dihydro-alkoxy-, dihydro-alkylthio-, and dihydro-alkylamino-benzyl-oxopyrimidines (DABOs, S-DABOs, and NH-DABOs) as potent and selective anti-HIV-1 agents belonging to the non-nucleoside reverse transcriptase inhibitor (NNRTI) class, we report here the synthesis and biological evaluation of a novel series of DABOs bearing a N,N-disubstituted amino group or a cyclic amine at the pyrimidine-C2 position, a hydrogen atom or a small alkyl group at C5 and/or at the benzylic position, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 57 publications
2
56
1
Order By: Relevance
“…The 2-Cl-6-F-N,N-DABOs were prepared following our reported procedures, [13,14] starting from 2-chloro-6-fluorophenylacetic or -phenylpropionic acid with a) N,N'-carbonyldiimidazole, b) potassium ethyl malonate or 2-methylmalonate in the presence of triethylamine and magnesium chloride, followed by acidic hydrolysis, and c) condensation of the obtained b-oxoesters with N,N-dimethylguanidine sulfate in the presence of sodium ethoxide (Scheme 1). Compounds MC1838 and MC1839, which share a chiral center at the benzylic position, were prepared and tested as racemates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-Cl-6-F-N,N-DABOs were prepared following our reported procedures, [13,14] starting from 2-chloro-6-fluorophenylacetic or -phenylpropionic acid with a) N,N'-carbonyldiimidazole, b) potassium ethyl malonate or 2-methylmalonate in the presence of triethylamine and magnesium chloride, followed by acidic hydrolysis, and c) condensation of the obtained b-oxoesters with N,N-dimethylguanidine sulfate in the presence of sodium ethoxide (Scheme 1). Compounds MC1838 and MC1839, which share a chiral center at the benzylic position, were prepared and tested as racemates.…”
Section: Resultsmentioning
confidence: 99%
“…[13,14] We have previously shown that 2,6-F 2 -N,N-DABO derivatives owe their potent inhibitory activity to their very high affinity for the NNBS. [13] However, their kinetics showed low association rates to HIV-1 RT, behaving as slow-binding/high-affinity inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…1), which is used in racemic form [12][13][14][15][16]. The synthesis of MC-1220 and its analogs was previously published by Mai et al [12] and Bartolini et al [13] by condensation of the corresponding b-keto esters with guanidine sulfate derivatives. The b-keto esters, however, were prepared through multistep reactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of MC-1220 and its analogs was previously published by Mai et al [12] and Bartolini et al [13] by condensation of the corresponding b-keto esters with guanidine sulfate derivatives. The b-keto esters, however, were prepared through multistep reactions [12]. Recently, Radi et al reported the synthesis of arylmethyl-functionalized S-DABOs and related analogs from C6-protected formyl pyrimidinone [17].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Among the NNRTIs, dihydroalkyloxybenzyloxopyrimidines (DABOs) were reported as potent HIV NNRTIs, with robust anti-HIV-1 activity against both the wild-type (wt) and a panel of clinically relevant HIV-1 mutants. [6] Three generations of DABO analogues have been found to date: dihydroalkyloxybenzyloxopyrimidines (O-DABOs), dihydroalkylthiobenzyloxopyrimidines (SDABOs), and dihydroalkylaminodifluorobenzyloxopyrimidines (N-DABOs), [7][8][9][10][11] from which many promising DABOs have been developed.…”
Section: Introductionmentioning
confidence: 99%